STATUS GIZI KAMBING KACANG DI KECAMATAN TANJUNG BINTANG KABUPATEN LAMPUNG SELATAN - Wicaksana, Kunaifi; ,, Muhtarudin; Widodo, Yusuf (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
This study was conducted in December 2014 in Tanjung Bintang District South Lampung Regency. This study aimed to determine the nutritional status of kacang goat based on the feedstuff consumed, crude protein content, and the management of feeding used by the kacang goat farmers in Tanjung Bintang District. This study used qualitative approach with survey method, then it was descriptively analyzed. Farmers interviewed came from six villages namely Jati Baru, Jati Indah, Trimulyo, Srikaton, Budilestari and Serdang. The result of this study showed the feedstuff mostly in the form of forage.Â Average dry matter consumption was 2.07 kg/goat/day, even the dry matter need was 0.61 kg/goat/day, and average protein consumption was 0.23 kg/goat/day, even the protein need was 0.07 kg/goat/day.Â Nutritional status of kacang goat in Tanjung Bintang district South Lampung Regency has fulfilled. Keywords: Â Kacang goat , crude protein requirement.